The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9040923
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of the Post-Thrombotic Syndrome

Abstract: The post-thrombotic syndrome (PTS) is a form of chronic venous insufficiency secondary to prior deep vein thrombosis (DVT). It affects up to 50% of patients after proximal DVT. There is no effective treatment of established PTS and its management lies in its prevention after DVT. Optimal anticoagulation is key for PTS prevention. Among anticoagulants, low-molecular-weight heparins have anti-inflammatory properties, and have a particularly attractive profile. Elastic compression stockings (ECS) may be helpful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 120 publications
(132 reference statements)
0
32
0
1
Order By: Relevance
“…The VS was developed for the purpose of diagnosing PTS, has proven inter-observer reliability, and is responsive to clinical change, but may be somewhat nonspecific. [9][10][11] Indeed, studies have reported that up to 40% of patients with PTS also have a high (>4) VS in the leg contralateral to DVT (cl-VS), which could reflect the presence of other conditions, most commonly primary venous insufficiency (PVI), rather than true PTS. [12][13][14] However, in those studies, cl-VS was assessed only once, either during the acute phase of DVT or during the follow-up phase after DVT, or in patients with a history of previous DVT.…”
Section: Introductionmentioning
confidence: 99%
“…The VS was developed for the purpose of diagnosing PTS, has proven inter-observer reliability, and is responsive to clinical change, but may be somewhat nonspecific. [9][10][11] Indeed, studies have reported that up to 40% of patients with PTS also have a high (>4) VS in the leg contralateral to DVT (cl-VS), which could reflect the presence of other conditions, most commonly primary venous insufficiency (PVI), rather than true PTS. [12][13][14] However, in those studies, cl-VS was assessed only once, either during the acute phase of DVT or during the follow-up phase after DVT, or in patients with a history of previous DVT.…”
Section: Introductionmentioning
confidence: 99%
“…Although anticoagulation therapy has proven to be effective and safe in preventing PE and recurrence of DVT and improving patients’ quality of life [ 3 , 4 ], DVT management is still facing challenging since anticoagulation alone does not resolve the thrombus formed in the vein. Consequently, approximately 25 ~ 50% of proximal DVT patients develop post-thrombotic syndrome (PTS) because of valve incompetence and long-term venous hypertension [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, approximately 25~50% of proximal DVT patients develop post-thrombotic syndrome (PTS) because of valve incompetence and long-term venous hypertension. 5 Catheter-directed thrombolysis (CDT) has been proposed for symptomatic patients with severe DVT, particularly in the setting of phlegmasia alba dolens. 6 Numerous studies reported the clinical bene t of CDT in the treatment of symptomatic DVT.…”
Section: Introductionmentioning
confidence: 99%